DISTRIBUTION AND GENERATION OF THE LEAF BEETLE XANTHOGALERUCA LUTEOLA (MÜLLER, 1766) IN LOCAL ECOSYSTEMS (Scientific journal of the Fergana State University, 2025)
This article examines the distribution, biological characteristics, and generation turnover of the leaf beetle Xanthogaleruca luteola (Müller, 1766) under conditions of the Fergana Valley. The study was conducted from April to November 2024 in both field and laboratory settings in the Fergana, Namangan, and Andijan regions. Special attention is paid to the beetle’s morphological traits—body structure, coloration, and diagnostic features—as well as its egg-laying behavior, larval stage, feeding habits, and pupal duration. The findings indicate that X. luteola may produce two or three generations per season, and the simultaneous presence of various developmental stages can cause significant damage to local ecosystems.